2020
DOI: 10.5897/ajps2020.2020
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of cultivated yam (Dioscorea species) in selected counties in Kenya

Abstract: This study was conducted to characterize Dioscorea spp. in Kenya using morphological and molecular characteristics. Data on 22 morphological traits were subjected to cluster analysis and multivariate analysis using principal component (PCA). The dendrogram of cluster analysis revealed three main groups: Species distribution based on PC-1 and PC-2 showed the distantly related species in each quarter; D. alata L. (1 st quarter), D. bulbifera L. (2 nd quarter), D. cayenensis Lam. (3 rd quarter) and D. minutiflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In the current study, the morphological traits that had a principal role in discriminating between the yam genotypes were tuber and aerial characteristics. Tese outcomes from the current study were in congruence with reports obtained by Valentine et al [15]. In their study, they revealed that the most astute traits were stem colour, leaf margin colour, leaf position, petiole colour, tuber shape, tuber surface texture, and tuber fesh colour.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the morphological traits that had a principal role in discriminating between the yam genotypes were tuber and aerial characteristics. Tese outcomes from the current study were in congruence with reports obtained by Valentine et al [15]. In their study, they revealed that the most astute traits were stem colour, leaf margin colour, leaf position, petiole colour, tuber shape, tuber surface texture, and tuber fesh colour.…”
Section: Discussionsupporting
confidence: 92%
“…From that study, no clear morphological variations were observed between the genotypes. Such eforts have also been made in Kenya where 22 morphological traits were used to evaluate diversity and reported close relatedness among the yam genotypes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the germplasm of D. bulbifera in Uganda has not been characterized, yet germplasm characterization is an initial step to conservation (Bioversity International, 2003). Elsewhere, several studies have been done to characterize morphological traits of Dioscorea species including D. alata L (Anokye et al, 2014), Amerindian yam (Beyerlein et al, 2018), and D. bulbifera (Atieno et al, 2020). Morphological traits are however less informative and exhibit a lot of variations attributed to agro-climatic fluctuations.…”
Section: Introductionmentioning
confidence: 99%